The Influence of Financial Technology (Fintech) on the Profitability of Banks Listed on the Indonesian Stock Exchange in the Period 2020 – 2023 - Dwiningsih, Sri; Ilyas, Sinar Billy; Ratnasari, Ike (Jurnal Ilmu Manajemen Advantage, 2025)
The author's objective in conducting this research is to analyze the influence of financial technology (FINTECH) on the profitability of banks listed on the Indonesia Stock Exchange for the 2020-2023 period. The author employed a quantitative method in conducting this research, utilizing secondary data from financial reports published by the Indonesia Stock Exchange. The sample for this study comprised eight banking companies over 4 years, selected purposively. The results of this study indicate that financial technology (FINTECH), as measured by e-banking, affects return on assets (ROA). This is because e-banking can reduce average operating and physical overhead costs for banks. Therefore, the availability of electronic banking services positively impacts bank profitability (return on assets). Financial technology (FINTECH), as indicated by e-banking, also affects the net interest margin (NIM) by reducing reliance on physical services (such as tellers and branches), thereby lowering bank operating costs. With lower operating costs, banks can maintain or increase profit margins from interest differentials. The ease of access and convenience of e-banking services encourage customers to hold their funds longer, thereby increasing third-party funds (TPF). This provides banks with a low-cost source of funds, reducing interest costs and positively impacting net interest income (NIM). However, this does not affect return on Equity (ROE) because e-banking cannot yet deliver the operational efficiencies of digital services and does not directly increase net income in proportion to Equity. This study contributes to the literature by identifying differences in the effects of e-banking across various dimensions of bank profitability and by revealing its limitations in increasing ROE, thereby highlighting an important gap for further research on more comprehensive fintech integration.